Pengaruh kualitas produk, fear of missing out (FOMO), dan daya tarik iklan terhadap keputusan pembelian produk Skintific di kalangan Gen Z - Regina, Amelia; Alshaf Pebrianggara (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
This study aims to analyze the effect of product quality, fear of missing out (FOMO), and advertising attractiveness on purchasing decisions for Skintific products among Generation Z. The rapid growth of the beauty industry on e-commerce platforms has intensified competition among brands, requiring companies to understand the factors influencing consumer purchasing behavior, particularly among Generation Z who are highly influenced by digital trends and social media. This study employed a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The sample comprised 96 Generation Z respondents in Sidoarjo who had purchased Skintific products on Shopee. The results indicate that product quality, FOMO, and advertising attractiveness have a positive and significant effect on purchasing decisions, both partially and simultaneously. These findings suggest that high product quality, psychological encouragement to follow trends, and attractive advertising can enhance consumer purchasing decisions. This study contributes to the literature on consumer behavior in the digital beauty industry and provides insights for companies seeking to develop effective marketing strategies to attract Generation Z consumers.